Implikasi Desain Kurikulum Melalui Kajian Literasi Bahasa Arab Siswa Madrasah Ibtidaiyah - Nurul Aini Latifah, Siti; Khoririn, Lukman; Aulia, Meivirda (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2024)
This research discusses the needs of students in learning Arabic language at Madrasah Ibtidaiyah, focusing on MI Islamiyah Kedungbondo, Balen Subdistrict, Bojonegoro. A qualitative research method was used involving a case study and participant students from grade 5. Data were collected through structured surveys covering students' skill levels, difficulties, and needs in Arabic language. The results showed variation in students' skill levels, with the majority at beginner to intermediate levels, and some facing difficulties in certain aspects. Students' needs include vocabulary improvement, understanding of grammar, and more fluent speaking skills. The implications of these findings are that teaching staff can design more effective learning strategies and adjust teaching methods to meet students' needs in learning Arabic language. This has significant implications for improving the quality of Arabic language education at Madrasah Ibtidaiyah.